Identification of a Novel Primary Atopic Disorder due to STAT6 Gain-of-Function Mutations - Safa Barış; Talal A. Chatila (Turkish Journal of Immunology)
Human inborn errors of immunity (IEI) are a group of distinct genetic disorders affecting children and adults, leading to recurrent infections, immune dysregulations, and malignancies. Over the course of the past decades, this area of research has witnessed significant progress in describing numerous monogenic disorders. A subset of IEI, which manifests as severe allergic disorders, recently termed "primary atopic disorders'', now encompasses over 30 monogenic defects. Notably, the Janus kinase (JAK)-signal transducer and activator of transcription 6 (STAT6) signaling pathway plays a pivotal role in mediating allergic responses and developing primary atopic disorders. Herein, we detail a newly described IEI disorder due to gain-of-function mutations in STAT6 associated with severe allergic dysregulation. We outline its underlying mechanisms and present therapeutic approaches to its management.